2015
DOI: 10.4038/ijms.v2i1.57
|View full text |Cite
|
Sign up to set email alerts
|

User-Age Classification Using Touch Gestures on Smartphones

Abstract: In this paper we investigated the possibility of classifying users' age-group using gesture-based features on smartphones. The features used were gesture accuracy, speed, movement time, and finger/force pressure. Nearest Neighbour classification was used to classify a given user's age-group. The 50 participants involved in this research included 25 elderly and 25 younger users. User-dependent and user-independent age-group classification scenarios were considered. On each scenario, two types of analysis were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…In a complementary case of our study [14], authors showed high classification rates between young adults (20-50 years) and older adults (70+ years) based on touch gestures, demonstrating differences in neuromotor skills during human ageing while our work studies differences between undeveloped neuromotor skills in children and total maturity in young adults.…”
Section: Introductionsupporting
confidence: 61%
“…In a complementary case of our study [14], authors showed high classification rates between young adults (20-50 years) and older adults (70+ years) based on touch gestures, demonstrating differences in neuromotor skills during human ageing while our work studies differences between undeveloped neuromotor skills in children and total maturity in young adults.…”
Section: Introductionsupporting
confidence: 61%
“…This section analyses quantitatively one of the many different potential applications of ChildCIdb. In particular, we focus on the popular task of children age group detection based on the interaction with mobile devices [7], [9], [10], [33]. Due to the large volume of information captured in ChildCIdb, we focus in this section only on the analysis of the Test 6 (Drawing Test) based on the way children colour a tree.…”
Section: Example Application: Age Detectionmentioning
confidence: 99%